A Longitudinal Study of Teamwork Quality in Design Teams. (May 2022) - Singh, H.; Horvat, N.; Škec, S.; Becattini, N.
Abstract: Teamwork quality (TWQ) is often associated with project success. Therefore, understanding TWQ is crucial to have better design project outcomes. Since most of the studies in the past have presented a cross-sectional analysis of TWQ, the current work focuses on capturing TWQ in a longitudinal way for a project-based learning (PBL) course. The results showed that the 6 facets differed significantly during the first half of the course than towards the end. In later phases of the PBL, TWQ and team performance were positively correlated than at the beginning.